Multi-parameter adjustment for high-precision azimuthal intersection positioning - Ai, Songtao; Wang, Shansi; Li, Yuansheng; Liu, Leibao (MethodsX, 2020)
The traditional azimuthal intersection method is viable for situations with only two control stations but a simple height averaging is not rigorous because the intersections vary in their distances from the two stations. In order to obtain the high-precision azimuthal intersections, this study presented a multi-parameter adjustment method, together with the Earth curvature correction and the atmospheric refraction correction models. This method is robust with varied distances between the control stations and the targeted intersections, without limitation of station quantity.•Based on the traditional space intersection, a multi-parameter adjustment model is added into the data processing for high-precision 3D positioning.•Both the Earth curvature error correction model and the atmospheric error correction model are included in the multi-parameter adjustment model, so the intersected points are more accurate than traditional intersections. [Display omitted]